2016
DOI: 10.4025/actasciagron.v38i2.27956
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of the flavonoid rutin on the biology of <i>Spodoptera frugiperda</i> (Lepidoptera: Noctuidae)

Abstract: ABSTRACT. The fall armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) is a major pest of maize crops in Brazil. The effects of plant metabolites on the biology and behavior of insects is little studied. The aim of the study was to evaluate the activity of rutin on the biology of the S. frugiperda by using artificial diets containing rutin. The study evaluated four treatments: regular diet (control group) and diets containing 1.0, 2.0 and 3.0 mg g -1 of rutin. The following biological variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 25 publications
2
37
0
5
Order By: Relevance
“…Studies have shown that the methanol extract of the leaves of E. pumila and the fraction from which rutin was isolated presented insecticidal activity (KUBO; VIEIRA; FUKUHARA, 1990;KUBO, 1991). Silva et al (2016) demonstrated that rutin extended the life cycle of larvae and pupae of the caterpillar Spodoptera frugiperda J. E. Smith, 1797 (Lepidoptera: Noctuidae); Guarda et al (2016) evidenced that a flavonoid was active against Aedes aegypti larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the methanol extract of the leaves of E. pumila and the fraction from which rutin was isolated presented insecticidal activity (KUBO; VIEIRA; FUKUHARA, 1990;KUBO, 1991). Silva et al (2016) demonstrated that rutin extended the life cycle of larvae and pupae of the caterpillar Spodoptera frugiperda J. E. Smith, 1797 (Lepidoptera: Noctuidae); Guarda et al (2016) evidenced that a flavonoid was active against Aedes aegypti larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Paiva et al (2016) observed that S. frugiperda completed the same stage in BX 1293 YG antibiosis resistant corn in 31.85 days. Larvae of S. frugiperda fed on artificial diet had their larval stage completed in 16 days (Silva et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, this practice contributes to unbalanced agroecosystems (Bernardi et al 2012) and the selection of insect resistant populations (Cruz et al 2010). The use of alternative pest control methods, such as plant resistance to insects, is an important component in an integrated pest management (IPM) approach (Jesus et al 2010a, b;Janini et al 2011;Silva et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Peres et al (2017) verified that quercetin present in Alibertia sessilis and A. intermedia influences the biology of Plutella xylostella causing deformity. Silva et al (2016b) verified that the rutin flavonoid negatively affected the biology of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) by prolonging the larval development time, reducing the weight of larvae and pupae and decreasing the viability of the pupae.…”
Section: Preparation Of Aqueous Extractsmentioning
confidence: 88%